Bullying pada Anak sebagai Permasalahan Sosial di Dunia Pendidikan dalam Perspektif Sosiologi: (Studi Kasus Bulliying Pendidikan dan Pelatihan Organisasi di Sekolah) - Donny Prastya (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2023)
Many students do bullying, nowadays. This paper discusses bullying activities in school organizations. Several concepts of social behavior are used to analyze how bullying practices occur, what are the motives and how bullying practices are interpreted by perpetrators. This study aims to determine the motives and causes of bullying at school, also the solutions offered to minimize bullying. This study uses the method of literature study. The research results show the fact that; first, the attitude of revenge from seniors causes higher bullying behavior in organizations in the school environment. Second, all bullies are victims of their seniors, so the victims turn into bullies. Third, the purpose of the victim being a bully is to repay the senior's mistreatment of his current junior. In addition, the perpetrator also bullied for the purpose of avenging himself, this is because the perpetrator was once a victim. Revenge is in the form of imitation of the treatment he received.